Membedah Stereotip Gender : Persepsi Karyawan terhadap Seorang General Manager pada Hotel Candi - Vhara diva wijaya (Universitas Harapan Medan, 2019)
Women who have a position as corporate leaders have more responsibility and are considered different compared to ordinary career women. The role of women is no longer limited to kitchen affairs, working in both the entrepreneurial and non-entrepreneurial sectors. Because women can also benefit by using their own network to get support where they work.This research was conducted on the employees of Candi Medan Hotel, data collection used to interview 6 hotel employees. This study uses qualitative research as research and phenomenology as a research approach. The samples taken in this study were 6 people, including 1 male manager, and 5 female and male employees. The person interviewed came from the same division to maximize the data obtained.The results of this study include: (1) the effectiveness of leadership by the female General Manager is considered good by employees. (2) leadership styles associated with communal traits adopted by general female managers (transformal leadership) are favored by employees. (3) the traits relate to gender do not affect the outcome of the evaluation and promotion give by the leaders.